Multi-Lineage Human iPSC-Derived Platforms for Disease Modeling and Drug Discovery - Sharma, Arun (Cell Stem Cell, 2020)
Human induced pluripotent stem cells (hiPSCs) provide a powerful platform for disease modeling and have unlocked new possibilities for understanding the mechanisms governing human biology, physiology, and genetics. However, hiPSC-derivatives have traditionally been utilized in two-dimensional monocultures, in contrast to the multi-systemic interactions that influence cells in the body. We will discuss recent advances in generating more complex hiPSC-based systems including three-dimensional organoids, tissue-engineered constructs, microfluidic organ-chip platforms, and humanized animal systems. While hiPSC differentiation still requires optimization, these next-generation multi-lineage technologies can augment the biomedical researcher’s toolkit and enable more realistic models of human tissue function.